Transcranial magnetic stimulation (TMS) safety: a practical guide for psychiatrists. (April 2018) - Taylor, Rohan; Galvez, Veronica; Loo, Colleen
Objectives: Repetitive transcranial magnetic stimulation (rTMS) is increasingly being utilised as a treatment option for depression, and with this comes a need for a practical review of safety issues intended for clinicians. This article provides an overview of the current literature regarding safety issues with rTMS for depression, and provides recommendations for clinical practice. Conclusions: Overall, rTMS is a well-tolerated treatment with common side effects (such as headache or local pain at the site of stimulation) being mild. Severe adverse effects, such as seizures, hearing impairment or mania, are uncommon. Certain populations, including adolescents, pregnant women, older adults and those with metal/electronic implants, require special consideration when prescribing and monitoring treatment courses. With adequate assessment and monitoring processes, rTMS can be administered safely in a large proportion of depressed patients.